Nutrient dynamics in litter mixtures of four Mediterranean maquis species decomposing in situ - Maisto, Giulia; De Marco, Anna; Meola, Angela; Sessa, Ludovica; Virzo De Santo, Amalia (Soil Biology and Biochemistry, 2011)
In natural conditions, litters shed from different species become mixed with each other, and decompose together. Most studies deal with decomposition of individual species; few studies investigate the inﬂuence of litter mixing on decomposition and nutrient dynamics; the results are contradictory as positive, negative, or no effect, of litter mixing have been observed. In this study we test the hypothesis: i) that litter mixing in the Mediterranean maquis, a nutrient poor, high diversity ecosystem, produces non-additive effects on nutrient dynamics; ii) that the effects vary with the composition in species of the mixture and with the relative amount of the species component the mixture. Two types of 3-species mixtures were set up; one contained three sclerophylls, Phillyrea angustifolia, Pistacia lentiscus and Quercus ilex; the other contained the ﬁrst two species with the mesophyll Cistus. Litterbags, containing monospeciﬁc litters and even and uneven mixtures, were incubated under natural condition in situ; even mixtures had the 3 species in equal proportion, whereas uneven mixtures had one of the species as dominant (50%) and the other two species in equal proportion (25%:25%). Litterbags were retrieved after 92, 188 and 403 days; litters from the mixtures were separately analyzed for mass loss and content of nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn). Results indicate that mixing inﬂuences the dynamics of N, Mn, Ca, Mg, Fe, Cu and Zn, but scarcely affects the dynamics of K and Na. The comparison of observed to expected values for changes of nutrients in litterbags indicates the occurrence of non-additive effects of litter mixing on movements of N, Fe, Cu, and Zn to or from the litterbags containing the mixtures. The effects depend on the composition in species of the mixture, whereas the relative amount of the species component the mixture is not relevant.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Interactions among litters; Lignin; litter decomposition; Manganese; Non-additive effects of litter mixing

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution